Flash flood susceptibility assessment using the parameters of drainage basin morphometry in SE Bangladesh. (20th February 2021) - Alam, Akhtar; Ahmed, Bayes; Sammonds, Peter
Abstract: Predicting the occurrence and spatial patterns of rainfall induced flash floods is still a challenge. Instant genesis and typically smaller areal coverage of the flash floods are the major impediments to their forecasting. Analysis of the morphometric parameters provides useful insight on hydrological response of the drainage basins to high intensity rainfall events. This information is valuable for understanding the flash flood potential of the drainage basins and for evading the destructions caused by the hazard. Here, we use eighteen morphometric parameters that influence the runoff volume, flow velocity, and inundation depth scenario of a flash flood. The analysis has been carried out for simulating the relative flash flood susceptibility of thirteen watersheds (B1 to B13) of variable sizes in southeastern Bangladesh. The morphometric parameters were derived from Digital Elevation Model (DEM) using Geographic Information System (GIS). The evaluated basin parameters include: area (A), perimeter (P), length (Lb), stream order (Su), stream number (Nu), stream length (Lu), stream frequency (Fs), drainage density (Dd), texture ratio (Rt), bifurcation ratio (Rb), basin relief (Hr), relief ratio (Rr), ruggedness number (Rn), time of concentration (Tc), infiltration number (If), and form factor (F). Two relative flash flood susceptibility scenarios were generated: (i) general watershed level, and (ii) more precise pixel level status. The watershed level comparison reveals that B4 and B6 watersheds constituting 72.61% of the total area are 'very high' susceptible, whereas the susceptibility of the other watersheds has been found as 'high' [B5 (6.95%)], 'moderate' [B8 and B13 (8.63%)], 'low' [B2, B10, B11 (4.64%)], and 'very low' [B1, B3, B7, B9, and B12 (7.18%)]. The derived watershed susceptibility map was subsequently integrated with two spatial analysis algorithms i.e., topographic wetness index (TWI) and topographic position index (TPI) through overlay analysis. The integration helped to understand the combined role of the general watershed morphometry and the in situ topography for determining the flash flood susceptibility of each spot (30 m × 30 m) within all the selected watersheds. The quantitative analysis and characterization of the watersheds from the perspective of flash flood hazard in this investigation is expected to be useful for implementing the site-specific mitigation measures and alleviating the effects of the hydrological hazard in the study area.